1977
DOI: 10.1136/jcp.30.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial radioisotopic kit for folate assays.

Abstract: SUMMARY A commercial kit for the radioisotopic assay of folate in serum, the Bio-Rad 'Quanta Count' folate kit, produced lower results than the Lactobacillus casei microbiological assay method.Its normal range was 2-0-13 0,ug/l and the reproducibility was similar to that of the microbiological assay method. The kit was also satisfactory for whole blood folate assays. The cost requires careful consideration before the kit is used for routine purposes.For many years most laboratories have depended upon a microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is not affected by prior administration of antibiotics or of antifolate drugs and the red cell folate need not previously be deconjugated. Numerous assay kits are now available and their performance compared with microbiological assay has been evaluated in several recent publications (Kubasik, Votosin & Sine 1975, Waddel et al 1976, Hill & Dawson 1977, McGown et al 1978. Although radioassay measures all the circulating folate rather than specific analogues, it tends to yield lower results-ranging from 50% (Rothenberg da Costa & Rosenberg 1972) to 90% (Waddel et al 1976) of those obtained by radioassay and iodinated kits have been found to give consistently lower values than tritiated kits (Kubasik et al 1975).…”
Section: T H E Causes Of Megaloblastic E R Y T H R O P O I E S I Smentioning
confidence: 99%
“…It is not affected by prior administration of antibiotics or of antifolate drugs and the red cell folate need not previously be deconjugated. Numerous assay kits are now available and their performance compared with microbiological assay has been evaluated in several recent publications (Kubasik, Votosin & Sine 1975, Waddel et al 1976, Hill & Dawson 1977, McGown et al 1978. Although radioassay measures all the circulating folate rather than specific analogues, it tends to yield lower results-ranging from 50% (Rothenberg da Costa & Rosenberg 1972) to 90% (Waddel et al 1976) of those obtained by radioassay and iodinated kits have been found to give consistently lower values than tritiated kits (Kubasik et al 1975).…”
Section: T H E Causes Of Megaloblastic E R Y T H R O P O I E S I Smentioning
confidence: 99%